Effect of glycation degree on the structure and digestion properties of ovalbumin: A study of amino acids and peptides release after in vitro gastrointestinal simulated digestion. (30th March 2022) - Yang, Qi; Wang, Ying; Yang, Meng; Liu, Xuanting; Lyu, Siwen; Liu, Boqun; Liu, Jingbo; Zhang, Ting
Graphical abstract: Highlights: The structure of ovalbumin was changed by different glycation degree. Glycation reduced protein digestibility, leading to the presence of large fragments after in vitro simulated digestion. The content of EAA and TAA released after digestion decreased, especially in the intestinal phase after adding trypsin. Peptide release and the distribution of peptide segments cleaved by trypsin were greatly influenced by glycation. Abstract: Glycation can improve the functional properties of protein. However, in vitro and animal studies have shown that glycation induced lysine blockage and impaired protein digestibility. This study aimed to explore the effects of different glycation degree on the structure and digestive characteristics of ovalbumin. The results showed that glycation decreased the turbidity and hydrophobicity of the protein and changed the protein structure. Moreover, the results of in vitro simulated digestion revealed that glycation reduced the contents of essential amino acids and total amino acids after digestion. Glycation changed the amino acids and peptides release from the protein by resisting the digestion of digestive enzymes, especially trypsin. In conclusion, this work links glycation, protein digestibility, and the release of amino acids and peptides. This emphasizes the importance of the balance between improving properties and ensuring the digestibility of proteins during food processing.